Study on pH and somatic cell count in milk of sub-clinical mastitic cows in association with udder and teat shape - K N WADHWANI, R H MODH, M M ISLAM D S NAURIYAL, R J MODI and (Indian Journal of Animal Production and Management, 2019)
Present experiment was conducted to study the pH and somatic cell count (SCC) in milk of mastitic cowsin association with udder and teat shape. Total 150 lactating Gir cows of different parities and at differentstages of lactation from different location of Anand district of Gujarat were randomly selected. Dairy farmswere visited in sequential manner and data were carefully collected personally. Cows were fed availablegreen and dry roughages, compounded concentrate mixture and handful of mineral mixture. Cleanwholesome drinking water was provided ad libitum to all the cows. Freshly drawn evening milk samples(approximately 10 ml) of all four quarters of all the150 experimental Gir cows were collected and subjectedto pH estimation and somatic cell count (SCC). pH reading was recorded by digital pH meter after calibrationof the pH probe. The pH level more than 6.8 indicated the incidence of subclinical mastitis. Laboratory testfor estimation of SCC was done using FossomaticTM Minor cell counter. Samples with more than 5,00,000SCC/ml of milk were considered as subclinical mastitis positive. There was elevation in milk pH value insubclinical mastitis (SCM) cows (7.1 ± 0.01) as compared to the healthy cows (6.65 ± 0.01). Among SCMcows with different shape of udder, cows with goaty udder had the highest milk pH values whereas cowswith round shape udder had minimum pH value. Similarly, SCM cows with cylindrical shape teat hadhigher milk pH than the SCM cows with funnel, bottle and pear shape teats. However, differences in milkpH value between right and left and fore and hind quarters of SCM cows were not appreciable. There waselevation in milk SCC in SCM cows (1802.48 ± 82.54 × 103) as compared to the healthy cows (122.46± 6.26 × 103). The SCC of milk samples collected from different udder and teat shape and right and leftquarter and fore and rear quarters showed similar pattern i.e., higher SCC in SCM cows as compared tohealthy cows. The study indicated that selection of Gir cows for trough and round udder may reduce themilk SCC and the incidences of subclinical mastitis.